Normal insulin-dependent activation of Akt/protein kinase B, with diminished activation of phosphoinositide 3-kinase, in muscle in type 2 diabetes - Young-Bum Kim; Svetlana E. Nikoulina; Theodore P. Ciaraldi; Robert R. Henry; Barbara B. Kahn (The Journal of Clinical Investigation, 1999)
To determine whether the serine/threonine kinase Akt (also known as protein kinase B) is activated in vivo by insulin administration in humans, and whether impaired activation of Akt could play a role in insulin resistance, we measured the activity and phosphorylation of Akt isoforms in skeletal muscle from 3 groups of subjects: lean, obese nondiabetic, and obese type 2 diabetic. Vastus lateralis biopsies were taken in the basal (overnight fast) and insulin-stimulated (euglycemic clamp) states. Insulin-stimulated glucose disposal was reduced 31% in obese subjects and 63% in diabetic subjects, compared with lean subjects. Glycogen synthase (GS) activity in the basal state was reduced 28% in obese subjects and 49% in diabetic subjects, compared with lean subjects. Insulin-stimulated GS activity was reduced 30% in diabetic subjects. Insulin treatment activated the insulin receptor substrate-1–associated (IRS-1–associated) phosphoinositide 3-kinase (PI 3-kinase) 6.1-fold in lean, 3.7-fold in obese, and 2.4-fold in diabetic subjects. Insulin also stimulated IRS-2–associated PI 3-kinase activity 2.2-fold in lean subjects, but only 1.4-fold in diabetic subjects. Basal activity of Akt1/Akt2 (Akt1/2) and Akt3 was similar in all groups. Insulin increased Akt1/2 activity 1.7- to 2.0-fold, and tended to activate Akt3, in all groups. Insulin-stimulated phosphorylation of Akt1/2 was normal in obese and diabetic subjects. In lean subjects only, insulin-stimulated Akt1/2 activity correlated with glucose disposal rate. Thus, insulin activation of Akt isoforms is normal in muscle of obese nondiabetic and obese diabetic subjects, despite decreases of approximately 50% and 39% in IRS-1– and IRS-2–associated PI 3-kinase activity, respectively, in obese diabetic subjects. It is therefore unlikely that Akt plays a major role in the resistance to insulin action on glucose disposal or GS activation that is observed in muscle of obese type 2 diabetic subjects.